The Relationship Of Mother's Knowledge About DPT Aefi To Compliance In Basic Immunization - Oky Rahma Prihandani; Ika Dyah Kurniati; Ulfa Wahyuningsih (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Background : Based on Riskesdas, child immunization data in Pati City in 2018 was Hepatitis B immunization 95.49%, BCG immunization 95.60%, DPT-Hib 1-3 immunization 76.33%, Polio immunization 89.24%, and Measles immunization 90.53%. The aim of this research was to determine the relationship between maternal knowledge about KIPI DPT and compliance with basic DPT immunization in Growong Kidul Village, Juwana District. Methods : This research is a descriptive observational study with a cross sectional approach, sampling was carried out using a random sampling method with inclusion and exclusion criteria, and data analysis used Spearman Rank. Result : In the study, 48 respondents (84.2%) were aged 20-35 years, 20 respondents (35.1%) had high school/vocational education, 40 respondents (70.2%) were housewives, 30 respondents (52.6%) had knowledge sufficient, and 47 respondents (82.5%) had timely DPT immunization for children. In the Spearman Rank test, the values obtained were p=0.001 and r=0.435, which means that there is a relationship between maternal knowledge and compliance with DPT basic immunization with a correlation of sufficient strength. Conclusion : Mother's knowledge is related to compliance with basic DPT immunization in Growong Kidul Village, Juwana District.